PhD supervision in Public Health - Regmi, Pramod R; Poobalan, Amudha; Simkhada, Padam; van Teijlingen, Edwin (Health Prospect, 2021)
Roles of PhD supervisors are diverse, ranging from providing in-depth discipline-specific Public Health knowledge and technical (e.g., methodological) support to the students, encouraging them towards publications or conference presentations, offering pastoral support for student wellbeing, and finally preparing them to defend their thesis by conducting a mock viva. Effective supervision plays a vital role in a PhD journey reflecting on the quality of the PhD work, positive PhD experience, and supervisor-student relationship. While some student-supervisors team may encounter conflicting and challenging relationships, many relationships between PhD supervisor(s) and students progress into mentorship through joint publications and grant applications, career advice, and support establishing wider collaborative networks. Drawing from the wider experiences of the authors, this article highlights the responsibilities, opportunities, and sometimes the challenging nature of being a PhD supervisor. This reflection will inform good practices for PhD supervisors in countries including Nepal, where the numbers of PhD students in the field of Public Health is steadily increasing.